The vegetables of the ancestors: The ritual botanical offerings of the Chancay culture in Cerro Colorado, Huaura valley - Dalen Luna, Pieter Van (2021)
Archaeological investigations with excavations carried out in the Cerro Colorado funerary area have made it possible to identify as part of the funerary contexts, abundant botanical remains placed inside ceramic deposits, which have been placed as part of the mortuary offerings at the same time of the ritual. funeral or time after. The identification of the botanical species reveals that edible parts of plants such as corn, were very recurrent, placed as part of the food of the dead.